Accuracy of AccessBio Immunoglobulin M and Total Antibody Rapid Immunochromatographic Assays for the Diagnosis of Acute Scrub Typhus Infection. - Blacksell, S; Jenjaroen, K; Phetsouvanh, R; Wuthiekanun, V; Day, N; Newton, P; Ching, WM (2010)
Using archived samples, we assessed the diagnostic capacity of a rapid immunochromatographic test (ICT) for the detection of Orientia tsutsugamushi IgM and total antibodies to aid with the diagnosis of acute scrub typhus infection in febrile patients in Laos. The sensitivity and the specificity of the ICT for the detection of IgM were 96.8% (121/125 samples; 95% confidence interval [CI], 92.1 to 99.1%) and 93.3% (98/105 samples; 95% CI, 86.7 to 97.3%), respectively. For the detection of total antibodies, the sensitivity was 97.6% (122/125 samples; 95% CI, 93.1 to 99.5%), but the specificity was much lower, at 71.4% (75/105 samples; 95% CI, 61.8 to 79.8%).